Intra‐arterial transplantation of HLA‐matched donor mesoangioblasts in Duchenne muscular dystrophy. Issue 12 (5th November 2015) - Cossu, Giulio; Previtali, Stefano C; Napolitano, Sara; Cicalese, Maria Pia; Tedesco, Francesco Saverio; Nicastro, Francesca; Noviello, Maddalena; Roostalu, Urmas; Natali Sora, Maria Grazia; Scarlato, Marina; De Pellegrin, Maurizio; Godi, Claudia; et al.
Abstract: Intra‐arterial transplantation of mesoangioblasts proved safe and partially efficacious in preclinical models of muscular dystrophy. We now report the first‐in‐human, exploratory, non‐randomized open‐label phase I–IIa clinical trial of intra‐arterial HLA‐matched donor cell transplantation in 5 Duchenne patients. We administered escalating doses of donor‐derived mesoangioblasts in limb arteries under immunosuppressive therapy (tacrolimus). Four consecutive infusions were performed at 2‐month intervals, preceded and followed by clinical, laboratory, and muscular MRI analyses. Two months after the last infusion, a muscle biopsy was performed. Safety was the primary endpoint. The study was relatively safe: One patient developed a thalamic stroke with no clinical consequences and whose correlation with mesoangioblast infusion remained unclear. MRI documented the progression of the disease in 4/5 patients. Functional measures were transiently stabilized in 2/3 ambulant patients, but no functional improvements were observed. Low level of donor DNA was detected in muscle biopsies of 4/5 patients and donor‐derived dystrophin in 1. Intra‐arterial transplantation of donor mesoangioblasts in human proved to be feasible and relatively safe. Future implementation of the protocol, together with a younger age of patients, will be needed to approach efficacy. Synopsis: This study reports a safe, first‐in‐human mesoangioblast cell therapy to treat Duchenne muscular dystrophy (DMD) in 5 young patients, using a successful preclinical strategy, as an exploratory non‐randomized open‐label phase I–IIa clinical trial of intra‐arterial HLA‐matched donor cell transplantation. Five patients affected by DMD were treated by intra‐arterial infusions of escalating doses of HLA‐matched donor mesoangioblasts. The trial was overall safe but showed minimal, if any, efficacy. Data analysis suggested to treat patients at an earlier stage of the disease, optimize in in vitro models each single step of the transplantation protocol, and use genetically corrected, autologous mesoangioblasts in a future trial. Abstract : This study reports a safe, first‐in‐human mesoangioblast cell therapy to treat Duchenne muscular dystrophy (DMD) in 5 young patients, using a successful preclinical strategy, as an exploratory non‐randomized open‐label phase I‐IIa clinical trial of intra‐arterial HLA‐matched donor cell transplantation.